2019
DOI: 10.1089/mdr.2019.0034
|View full text |Cite
|
Sign up to set email alerts
|

Resistome and a NovelblaNDM-1-Harboring Plasmid of anAcinetobacter haemolyticusStrain from a Children's Hospital in Puebla, Mexico

Abstract: Acinetobacter calcoaceticus-baumannii complex isolates have been frequently associated with hospital and community infections, with A. baumannii being the most common. Other Acinetobacter spp. not belonging to this complex also cause infections in hospital settings, and the incidence has increased over the past few years. Some species of the Acinetobacter genus possess a great diversity of antibiotic resistance mechanisms, such as efflux pumps, porins, and resistance genes that can be acquired and disseminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that a 4609-bp circular intermediate occurs in p34AB ( He et al., 2020b ). IS 91 was previously considered a rare element in the transfer of resistance genes, but it has been increasingly detected in recent studies ( Bello-López et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that a 4609-bp circular intermediate occurs in p34AB ( He et al., 2020b ). IS 91 was previously considered a rare element in the transfer of resistance genes, but it has been increasingly detected in recent studies ( Bello-López et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms of resistance to carbapenems in A. baumannii include overexpression of efflux Abbreviations: AMR, Antimicrobial resistance; CRAB, Carbapenem-resistant Acinetobacter baumannii; GHRU, Global Health Research Unit; IC, International clone; ICU, Intensive care unit; MLST, Multi-locus sequence typing; OAUTHC, Obafemi Awolowo University Teaching Hospitals Complex; OR, Odds ratio; SNP, Single nucleotide polymorphism; UCH, University College Hospital; VFDB, Virulence factor database; WGS, Whole genome sequencing. pumps, membrane porin modification and, most prominently, possession of resistance genes, particularly the OXA-and NDMtype carbapenemases, which are borne on either plasmids or chromosomes (2,10,11). Resistance to carbapenems is associated with the successful and globally disseminated major A. baumannii clones, international clones (ICs) 1-3, with very high resistance rates reported (12).…”
Section: Introductionmentioning
confidence: 99%
“…To study the genome architecture of the emerging pathogen A. haemolyticus , we constructed a data set consisting of the genome sequences of 31 Mexican isolates described here and a previously sequenced Mexican A. haemolyticus ( Bello-López et al, 2019 ) (in total, 9 Mexican strains now have finished chromosomes) and 19 putative A. haemolyticus complete genome sequences available in NCBI RefSeq database (4 of them were finished assemblies), which were isolated from hospitals in different countries. To confirm the species designation of all the genomes in the collection, and to detect equivalent strains, we calculated the average nucleotide identity (ANI) between all genome pairs.…”
Section: Resultsmentioning
confidence: 99%
“…A. haemolyticus has been implicated in serious infections, frequently in those linked to the nosocomial environment ( Ko et al, 2007 ; Gundi et al, 2009 ; Turton et al, 2010 ; Fu et al, 2012 ; Schleicher et al, 2013 ; Wang et al, 2014 ; Jeong et al, 2016 ). Moreover, recent reports indicate that this pathogen is acquiring very efficient carbapenem-resistance determinants, such as the bla NDM-1 gene, worldwide ( Fu et al, 2012 ; Jones et al, 2015 ; Bello-López et al, 2019 ; Jiang et al, 2019 ). All these characteristics suggest that A. haemolyticus may have the potential to become a threatening pathogen, following a path similar to that of A. baumannii .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation